2014
DOI: 10.3109/02713683.2014.900806
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of α-Smooth Muscle Actin Expression and Migration of Pterygium Fibroblasts by Coculture with Amniotic Mesenchymal Stem Cells

Abstract: These results suggested that hAMSCs have the potential to inhibit the generation and invasiveness of pterygium in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…Since smooth muscle cells seemed to be the most significantly enriched cell type in pterygia, the expression of known markers of smooth muscle cells as well as of myofibroblasts (34,35) was analyzed, the latter being not included within the xCell algorithm (Figure 2B). The results indicated that myofibroblasts represent the most differentially enriched cell type in pterygium specimens, which supports their assumed role in the pathogenesis of the disease (2,35,(40)(41)(42). Current evidence suggests that myofibroblasts emerge from conjunctival epithelial cells through the process of epithelial-mesenchymal transition (3,35).…”
Section: Discussionsupporting
confidence: 52%
“…Since smooth muscle cells seemed to be the most significantly enriched cell type in pterygia, the expression of known markers of smooth muscle cells as well as of myofibroblasts (34,35) was analyzed, the latter being not included within the xCell algorithm (Figure 2B). The results indicated that myofibroblasts represent the most differentially enriched cell type in pterygium specimens, which supports their assumed role in the pathogenesis of the disease (2,35,(40)(41)(42). Current evidence suggests that myofibroblasts emerge from conjunctival epithelial cells through the process of epithelial-mesenchymal transition (3,35).…”
Section: Discussionsupporting
confidence: 52%
“…Moreover, researches also indicate that ACTA2 potentiates metastatic potential of human lung cancer cells via enhancing actin filament assembling [12,13]. In addition, investigations delineate that ACTA2 could improve the migration potential of fibroblasts and mesenchymal stem cells [14][15][16]. Whether ACTA2 expresses in NSCs and its role in NSC migration still remain unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Coculture of human amniotic mesenchymal stem cells (hAMSCs) with pterygium fibroblasts also showed the anti‐EMT effect by inhibition of α‐smooth muscle actin. Also, proximity with hAMSCs led to a diminution in the migratory phenotype of pterygial fibroblasts (Sha et al, ). These findings elucidated how hAMSCs are preventing the development of pterygium through abrogating TGFβ and the Notch signaling pathways.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
“…The normal arrows show the role of signaling in pterygium which have been indicated in previous works, but the dotted arrows show the signaling roles which only confirmed in cancer cells and it is suggested to investigate in pterygium cases. APC: antigen-presenting cell; EGFR: epidermal growth factor receptor; EMT: epithelial−mesenchymal transition; miR: microRNA; MMP: metalloproteinase; mTOR: mammalian target of rapamycin; NF-κB: nuclear factor-κB; PI3K: phosphoinositide 3-kinase; PTEN: phosphatase and tensin homolog; TCF4: transcription factor 4; TGFβ: transforming growth factor β; TNF-α: tumor necrosis factoruPA, urokinase-type plasminogen activator; Zeb1: zinc finger E-box binding homeobox 1 [Color figure can be viewed at wileyonlinelibrary.com] phenotype of pterygial fibroblasts(Sha et al, 2014). These findings elucidated how hAMSCs are preventing the development of pterygium through abrogating TGFβ and the Notch signaling pathways.Pirfenidone, which is known as a potential antifibrotic drug, has shown inhibitory effects on proliferation and migration on pterygium fibroblasts through diminishing expression of TGFβ at the protein level in a dose-dependent manner.…”
mentioning
confidence: 99%